2017
DOI: 10.21037/atm.2016.12.69
|View full text |Cite
|
Sign up to set email alerts
|

The mycobiome of the human urinary tract: potential roles for fungi in urology

Abstract: Abstract:The mycobiome, defined as the fungal microbiota within a host environment, is an important but understudied component of the human microbial ecosystem. New culture-independent approaches to determine microbial diversity, such as next-generation sequencing methods, have discovered specific, characteristic, commensal fungal populations present in different body sites. These studies have also identified diverse patterns in fungal communities associated with various diseases. While alterations in urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 85 publications
0
56
0
Order By: Relevance
“…We found that the number of fungal sequence reads were lower than that of bacterial sequence reads, which also agrees with published studies showing that the number of fungal sequences are usually lower than that of bacterial sequences, with only ∼0.1% of detectable sequences in the total gut microbiota attributed to fungi and 99% to bacteria [ 18 , 19 ]. Detection of lower number of fungal reads in a sample has been attributed to the fact that fungal signatures are more sensitive to DNA isolation method than bacterial signature [ 20 ] and limitations of the fungal sequencing databases used for identity assignments [ 21 , 22 ]. However, in spite of these limitations, our analysis provides valuable insight into the potential clinical relevance of the bacteriome/mycobiome in oral tongue cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the number of fungal sequence reads were lower than that of bacterial sequence reads, which also agrees with published studies showing that the number of fungal sequences are usually lower than that of bacterial sequences, with only ∼0.1% of detectable sequences in the total gut microbiota attributed to fungi and 99% to bacteria [ 18 , 19 ]. Detection of lower number of fungal reads in a sample has been attributed to the fact that fungal signatures are more sensitive to DNA isolation method than bacterial signature [ 20 ] and limitations of the fungal sequencing databases used for identity assignments [ 21 , 22 ]. However, in spite of these limitations, our analysis provides valuable insight into the potential clinical relevance of the bacteriome/mycobiome in oral tongue cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is based on the long-held dogma that urine is sterile. Recently, however, researchers have used next-generation sequencing and enhanced culture methods to detect communities of bacteria, fungi, and viruses (microbiota) in catheterized urine collected directly from the female bladder [ 89 95 ]. Thus, the “sterile urine” paradigm is no longer valid.…”
Section: Cell Populations In or Associated With The Lutmentioning
confidence: 99%
“…Targeted analysis of fungi using multi-locus PCR coupled with electrospray ionization/mass spectrometry revealed increased fungal DNA during symptomatic flares in patients with IC/BPS [33, 34•]. Fungal community profiling by NGS using the ITS1 region of fungal rRNA, however, revealed that the taxa detected in previous studies are only a small component of the complement of genera present in urinary specimens [35,36].…”
Section: Non-bacterial Organismsmentioning
confidence: 99%